ANALISIS KAIDAH AL-BADAL PADA RASM ‘UTSMĀNĪ DALAM MUṢḤAF AL-QUR’AN: STUDI PUSTAKA ILMU RASM - Raudhatul Fidyani; Afnan Mu’adzah; Misnawati Misnawati (JIQTA: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This study examines the concept of al-Badal within the Utsmanic script (rasm ‘Utsmānī) as an essential component of the Qur’anic manuscript writing system. Al-Badal refers to the substitution of one letter for another in specific words whose orthography differs from that of the standard Arabic script (rasm Imlā’ī). The aim of this research is to explain the definition, theoretical foundations, and applications of al-Badal in selected words found in the Utsmanic muṣḥaf. This study employs a library research method by analyzing classical and contemporary literature on Qur’anic orthography as well as relevant modern studies. The findings indicate that letter substitution in al-Badal is not a deviation in writing but reflects linguistic, phonetic, and semantic considerations that preserve the diversity of qirā’āt and the authenticity of the revealed text. The study highlights that the Utsmanic script possesses a unique and purposeful writing system that continues to be maintained in modern Qur’anic manuscripts